Examples
−45x+125=0
Step 1
Subtract 125 from both sides of the equation.
−45x=−125
Step 2
Move the negative in front of the fraction.
−45x=−125
Step 3
Step 3.1
Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.
5x,25
Step 3.2
Since 5x,25 contains both numbers and variables, there are two steps to find the LCM. Find LCM for the numeric part 5,25 then find LCM for the variable part x1.
Step 3.3
The LCM is the smallest positive number that all of the numbers divide into evenly.
1. List the prime factors of each number.
2. Multiply each factor the greatest number of times it occurs in either number.
Step 3.4
Since 5 has no factors besides 1 and 5.
5 is a prime number
Step 3.5
25 has factors of 5 and 5.
5⋅5
Step 3.6
Multiply 5 by 5.
25
Step 3.7
The factor for x1 is x itself.
x1=x
x occurs 1 time.
Step 3.8
The LCM of x1 is the result of multiplying all prime factors the greatest number of times they occur in either term.
x
Step 3.9
The LCM for 5x,25 is the numeric part 25 multiplied by the variable part.
25x
25x
Step 4
Step 4.1
Multiply each term in −45x=−125 by 25x.
−45x(25x)=−125(25x)
Step 4.2
Simplify the left side.
Step 4.2.1
Cancel the common factor of 5x.
Step 4.2.1.1
Move the leading negative in −45x into the numerator.
−45x(25x)=−125(25x)
Step 4.2.1.2
Factor 5x out of 25x.
−45x(5x(5))=−125(25x)
Step 4.2.1.3
Cancel the common factor.
−45x(5x⋅5)=−125(25x)
Step 4.2.1.4
Rewrite the expression.
−4⋅5=−125(25x)
−4⋅5=−125(25x)
Step 4.2.2
Multiply −4 by 5.
−20=−125(25x)
−20=−125(25x)
Step 4.3
Simplify the right side.
Step 4.3.1
Cancel the common factor of 25.
Step 4.3.1.1
Move the leading negative in −125 into the numerator.
−20=−125(25x)
Step 4.3.1.2
Factor 25 out of 25x.
−20=−125(25(x))
Step 4.3.1.3
Cancel the common factor.
−20=−125(25x)
Step 4.3.1.4
Rewrite the expression.
−20=−x
−20=−x
−20=−x
−20=−x
Step 5
Step 5.1
Rewrite the equation as −x=−20.
−x=−20
Step 5.2
Divide each term in −x=−20 by −1 and simplify.
Step 5.2.1
Divide each term in −x=−20 by −1.
−x−1=−20−1
Step 5.2.2
Simplify the left side.
Step 5.2.2.1
Dividing two negative values results in a positive value.
x1=−20−1
Step 5.2.2.2
Divide x by 1.
x=−20−1
x=−20−1
Step 5.2.3
Simplify the right side.
Step 5.2.3.1
Divide −20 by −1.
x=20
x=20
x=20
x=20